2002
DOI: 10.4049/jimmunol.169.11.6127
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Augmentation of the Synthetic Ligand- Mediated Function of Mouse NK1.1 Ag+ T Cells: Their Cytokine Production and Hepatotoxicity In Vivo and In Vitro

Abstract: We recently reported that the direct antitumor effectors in the liver induced by α-galactosylceramide (α-GalCer) are NK cells that are activated by the IFN-γ produced from NK1.1 Ag+ T cells (NKT cells) specifically stimulated with α-GalCer, whereas NKT cells cause hepatocyte injury through the Fas-Fas ligand pathway. In the present study, we investigated how mouse age affects the α-GalCer-induced effect using young (6-wk-old), middle-aged (30-wk-old), and old (75-wk-old) mice. The serum IFN-γ and IL-4 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
7
63
0
Order By: Relevance
“…11). However, in this work, we could clearly show that IFN-␥ is not pivotal for ␣-GalCer-induced hepatotoxicity, which is consistent with recently published results (32). Unexpectedly, IFN-␥ neutralization even aggravated liver injury in this model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…11). However, in this work, we could clearly show that IFN-␥ is not pivotal for ␣-GalCer-induced hepatotoxicity, which is consistent with recently published results (32). Unexpectedly, IFN-␥ neutralization even aggravated liver injury in this model.…”
Section: Discussionsupporting
confidence: 93%
“…Because both cytokines are induced upon ␣-GalCer treatment, with the time course of ␣-GalCer-induced IFN-␥ expression resembling that of ALT release, we analyzed the effect of neutralizing Abs against these cytokines in the ␣-GalCer model. Surprisingly, neutralization of IFN-␥ not only failed to block ␣-GalCer-mediated hepatic injury, as had already been previously described (32), but even caused an increased ALT release (Fig. 3A).…”
Section: Relevance Of ␣-Galcer-induced Cytokines For Liver Injurysupporting
confidence: 82%
“…In general, however, both the quantitative and functional deficiency of NKT cells (when tested) in these studies was not as profound as that found in this population of MDS patients. The impact of age or sex on NKT function in humans is not clear, although an increase in NKT function has been suggested in older mice (Inui et al, 2002). Recent studies showed that NKT function was preserved in patients with monoclonal gammopathy , who had a similar age distribution to the MDS patients in the present study.…”
Section: Resultssupporting
confidence: 48%
“…1B). Previously, we found that NKT cell activities after a-GalCer stimulation increase age-dependently, while those after anti-CD3 Ab stimulation are independent of age [25]. Obviously a-GalCer stimulates mouse NKT cells in a CD1d-dependent manner [26].…”
Section: Discussionmentioning
confidence: 78%